Is there a business case for early generation seed? - International Potato Center (2016)
National Agricultural Research Institutes in 11 Sub-Saharan African countries expanded their pre-basic sweetpotato seed production. Ten institutions started to implement their business plans; of which six earned revenues from the seed sales to start revolving funds.